Investigation of the effect of mindfulness on sexual desire and sexual satisfaction in primigravida pregnant women - Shamim Saniei; Fariba Fahami; Rahele Samouei; Hatav Ghasemi Tehrani (Wolters Kluwer Medknow Publications, 2022)
BACKGROUND: Pregnancy causes a set of complex physiological and psychological changes that affect marital relationships. Mindfulness is a form of meditation that can promote person's performance and perception of sexual relationships. The present study aimed to determine the effect of mindfulness on sexual desire and sexual satisfaction in primigravida pregnant women. MATERIALS AND METHODS: The present study is a quasi-experimental that has investigated on 72 primigravida pregnant women. The samples were selected randomly and assigned to experimental and control groups. The experimental group received six 90-min sessions of mindfulness intervention, and the control group received the educational pamphlet. The female sexual function index (FSFI) was filled by the subjects of the two groups in three stages of before the intervention, a week, and a month after the intervention. Data analysis was done by SPSS20 (Statistics 20 software; SPSS Inc., Chicago, IL, USA) at the significance level of 0.05. RESULTS: According to the statistical tests, there was no significant difference between the two groups in terms of demographic characteristics and pregnancy information. The findings suggest no significant difference between the mean pretest and posttest score of sexual desire in the two groups (P > 0.05). However, the two groups were significantly different in terms of the mean score of sexual satisfaction before and after the intervention (P<0.05). CONCLUSION: By increasing the concentration on the present moment and avoiding judgment, mindfulness can increase sexual satisfaction. However, sexual desire can be affected by various factors such as the cultural context, the quality of marital relationships, and the pregnancy hormonal changes that can influence the sexual response.